Peningkatan Keterampilan Public speaking melalui Pelatihan Kader Pelajar Nahdlatul Ulama Kecamatan Cisurupan - Rahmanurwahidah, Rahmanurwahidah; Nurhadi, Zikri Fachrul (Penerbit Goodwood, 2024)
Purpose: This article discusses improving public speaking skills through training for Nahdlatul Ulama cadres in Cisurupan District. The main aim of this article is to improve good public speaking skills, so that later IPNU-IPPNU Cisurupan District cadres will be able to convey ideas, thoughts and messages more effectively and convincingly. Methodology: In its implementation, a structured and focused training approach was carried out to improve the public speaking skills of Nahdlatul Ulama cadres in Cisurupan District. The flow of activity stages consists of 4 main stages, namely Planning, Observation, Implementation and Evaluation. Results: Through this training activity, participants can understand theoretically and practically the basics of public speaking. With this service, it is hoped that we will be able to convey messages clearly, convincingly and attractively to the public. Apart from that, mastering basic public speaking techniques can also increase participants' self-confidence so they are able to perform better in public. Conclusions: This training activity successfully achieved its goal of improving participants' skills to boost their confidence in their abilities. It is also hoped that the results of this service can serve as a foundation for continuously enhancing effective communication skills among Nahdlatul Ulama students as well as the general public. Limitations: This activity does not use audio visual media so that the presentation of material and practice is a bit hampered. Therefore, for the next activity, audio visual media such as a projector, microphone and sound system are needed. Contribution: Public speaking skills training has had a positive impact in improving public speaking skills among Nahdlatul Ulama student cadres in Cisurupan District.